Flexural properties of the composites polystyrene/fiber natural Alfa treated - MEGHLAOUI, Bahia (Biopolymer Applications Journal, 2026)
<audio class="audio-for-speech"></audio> Translator <audio class="audio-for-speech"></audio> Translator The influence of chemical treatment on the flexural properties of Polystyrene/plant fiber composites has been studied. The Alfa fiber is used as reinforcement after been treated with a NaOH aqueous solution 3% for 24, 48 and 72 hours at 25°C. The results obtained show that the chemical modification of the Alfa fiber affects the mechanical properties of the composites. The flexural strength and flexural modulus were clearly improved with the treatment compared to the composites with the untreated fiber. In addition, an increase of the mechanical properties is observed with the increase of the treatment time. This improvement in the flexural properties is attributed to the good adhesion between the matrix and the reinforcement. SEM results show that treated Alfa fiber with 3% NaOH for 72 h makes the fiber surface smooth after removal of the non-cellulosic components and the water absorption rate decreases with the during treatment. This decrease is due to the reduction of hydroxyl groups in the fiber, following the removal of amorphous compounds.